GRID2 a novel gene possibly associated with mevalonate kinase deficiency. - Moura, Ronald; Tricarico, Paola Maura; Campos Coelho, Antonio Victor; Crovella, Sergio (Rheumatol Int, 2015)
Mevalonate kinase deficiency (MKD) is a rare autosomal disease caused by mutations in the mevalonate kinase gene (MVK). The genotype-phenotype correlation is sometimes problematic due to the great genetic and clinical heterogeneity; so we hypothesize that genes other than MVK are able to modulate MKD clinical phenotypes. This hypothesis was tested by analyzing the exome of 22 patients with MKD all carrying MVK gene mutations, and 20 patients with recurrent fevers (RF) not carrying MVK mutations. Our preliminary findings suggest a possible role of GRID2 in the susceptibility to develop MKD. GRID2 gene (4q22.2), encoding for human glutamate receptor delta-2, associated with MKD: The rs1450500 SNP was differently distributed in patients with MKD with respect to those with RF. Being aware of the small number of patients analyzed, we hypothesized a possible role for GRID2 as possible phenotype modifier in MKD patients, especially in those with severe phenotypes.